Evaluation of chemical profile and antioxidant potential of Trichodesma indicum (L.) R.Br. - Mahendra S Khyade,; Subhash N Varpe,; Anup D Padwal, (International Journal of Phytomedicine, 2017)
The present study was conducted to evaluate the antioxidant activity and chemical composition of aqueous methanolic extract of Trichodesma indicum (L.) R.Br. The extract was tested for antioxidant activity using various in vitro models viz., DPPH, ABTS, NO, FRAP, total antioxidant activity and reducing power. The total phenolic and flavonoid contents were found to be equivalents to 97.83 ± 0.08 µg of gallic acid and 45.45 ± 0.19 µg of rutin /mg of dried aqueous methanolic extract, respectively. Among various antioxidant assays performed, maximum inhibition was observed in the ABTS (IC50 17.13 ± 0.23 μg) followed by DPPH (IC50 80.64 ± 0.29 μg) and NO (IC50 4.12 ± 0.02 μg) assay. GC-MS analysis revealed the presence of over 38 compounds, the prevailing compounds were hexadecanoic acid, β-sitosterol, ethyl iso-allocholate and 9,12,15,-Octadecatrienoicacid. The HPLC analysis further confirmed the presence of rutin, salicylic acid and benzoic acid. This confirms that T. indicum could be the good source of natural antioxidant for industrial and pharmaceutical preparations.